عُمان وعصر النبوّة - يونس محسن (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
عُمان قطر عربي يقع في الجنوب الشرقي من شبه الجزيرة العربية , وهو يتمتع بموقع استراتيجي مهم, سواء أكان ذلك من الناحية الجغرافية أم الاقتصادية أم السياسية , وقد شغلت عمان دوراً حضارياً متصل الحلقات منذ الألف الرابع قبل الميلاد حتى ظهور الدعوة الإسلامية بالحجاز وكان أهل هذه البلاد سباقين إلى اعتناق الإسلام بالرغم من المسافات التي كانت تفصلهم عن مكة المكرمة/ مركز انطلاق الدعوة. وقد لبوا نداء النبي محمد صلي الله عليه وسلم, فاعتنقوا الإسلام, وأسهموا بفاعلية في بناء الدولة الإسلامية الأولى . وفي هذه المقالة سنحاول إلقاء الضوء على الدور الذي أداه العُمانيون في هذه الفترة التاريخية من قيام الدولة الإسلامية. Oman is an Arab country located in the eastern south of the Arabian Peninsula. It is endowed with a strategically important geographic, economic and political location. Oman has maintained a continuous cultural role from 4000 B.C. until the dawn of Islam in Hedjaz. The Omanis were forerunners in embracing the new emergent religion despite the huge distance separating them from Mecca, the centre of Islam. They answered the call of the prophet (p.b.u.h) in embracing the new religion and, later, making substantial contributions to the establishment of the first Islamic State. We will attempt in this paper to highlight the role played by the Omanis during the historical period pertaining to the establishment of the Islamic State.